'I was trying to get there, but I couldn't': social norms, vulnerability and lived experiences of home delivery in Mashonaland Central Province, Zimbabwe. Issue 9 (17th June 2021) - Webb, Karen A; Mavhu, W; Langhaug, L; Chitiyo, V; Matyanga, P; Charashika, P; Patel, D; Prost, A; Ferrand, Rashida A; Bernays, S; Cislaghi, B; Neuman, M
Abstract: Increasing facility-based delivery rates is pivotal to reach Sustainable Development Goals to improve skilled attendance at birth and reduce maternal and neonatal mortality in low- and middle-income countries (LMICs). The translation of global health initiatives into national policy and programmes has increased facility-based deliveries in LMICs, but little is known about the impact of such policies on social norms from the perspective of women who continue to deliver at home. This qualitative study explores the reasons for and experiences of home delivery among women living in rural Zimbabwe. We analysed qualitative data from 30 semi-structured interviews and 5 focus group discussions with women who had delivered at home in the previous 6 months in Mashonaland Central Province. We found evidence of strong community-level social norms in favour of facility-based delivery. However, despite their expressed intention to deliver at a facility, women described how multiple, interacting vulnerabilities resulted in delivery outside of a health facility. While identified as having delivered 'at home', narratives of birth experiences revealed the majority of women in our study delivered 'on the road', en route to the health facility. Strong norms for facility-based delivery created punishments and stigmatization for home delivery, which introduced additional risk to women at the time of delivery and in the postnatal period. These consequences for breaking social norms promoting facility-based delivery for all further increased the vulnerability of women who delivered at home or on the road. Our findings highlight that equitable public health policy and programme designs should include efforts to actively identify, mitigate and evaluate unintended consequences of social change created as a by-product of promoting positive health behaviours among those most vulnerable who are unable to comply.